Tourist friendly tourism information system - Ambrož, Milan; Ambrož, Domen (Hotel and Tourism Management, 2014)
The globalisation of world economy accelerated the processes of regional cooperation in the field of tourism. Slovenia is a small tourist destination with many not yet exploited tourism potentials. For many years there has been extensive cooperation with neighbouring countries and regions in the field of tourism. Because of many differences between regional players in the field of tourism, not substantial progress has been made. Recent initiatives from the tourist players from the Danube region countries promise new developments. Summits and meetings among regional players show that there are creative but scattered initiatives to build an effective and integral tourist information system. In this paper we propose a prototype of a holistic tourist information system that bridges regional differences and establishes a solid base for the tourist information sharing, for the exchange of tourists and for the building of the comprehensive tourism value constellation on the national and regional level.